2009
DOI: 10.3354/meps08245
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and compositional correlates of growth rate in deep-water bamboo corals (Gorgonacea; Isididae)

Abstract: Little is known about the factors that affect the growth rates of deep-water corals. Analysis of 23 specimens of bamboo corals, a ubiquitous deep-water group, that were reliably aged using radiometric techniques or validated increment counts indicates that the radial growth rate of the coral's calcite internode declines with depth and increases logistically with ambient temperature. Temperature alone accounts for about half of the variance among specimens in lifetime mean growth rates. Growth rates plateau bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
3
18
1
Order By: Relevance
“…The mean growth rate is in between 45 µm and 75 µm per year, in agreement with others estimates [43][44][45]. However, the first 10 mm of the specimen exhibited faster growth compared to that of the next 20 mm.…”
Section: Description Of the Corals Measured In The Studysupporting
confidence: 78%
See 3 more Smart Citations
“…The mean growth rate is in between 45 µm and 75 µm per year, in agreement with others estimates [43][44][45]. However, the first 10 mm of the specimen exhibited faster growth compared to that of the next 20 mm.…”
Section: Description Of the Corals Measured In The Studysupporting
confidence: 78%
“…A focused O − ion beam of about 10 nA was used to analyze the samples. Ions of 7 Li + , 23 Na + , 24 Mg + , 44 Ca + and 88 Sr + were measured using a −70 eV energy filtering after a presputtering time of 2 min, in monocollection mode on an electron multiplier. The possible isobaric interference of 88 Sr 2+ on 44 Ca + was checked by measuring the mass 43.5 ( 87 Sr 2+ ) and was observed as negligible.…”
Section: Trace Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent studies, such as those performed on Gerardia sp. and bamboo corals, have assessed the growth of CWC from the Atlantic and Pacific oceans, as well as the Caribbean Sea (Matsumoto 2007, Andrews et al 2009, Parrish & Roark 2009, Thresher 2009) and found very slow growth rates of a few micrometres in radial growth per year. However, a higher axial growth rate of 0.5 to 1 cm yr -1 was estimated for large and old bamboo coral colonies.…”
Section: Introductionmentioning
confidence: 99%